Pengembangan Sistem Deteksi Kualitas Udara Berbasis Sensor IoT Menggunakan Fitur Notifikasi Telegram di Terminal Tingkir, Salatiga - Pariama, Alberth; Efendi, Rissal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Climate change and air pollution are two of the world’s most pressing issues that have a major impact on ecosystems and human health. The aim of this study is to create an internet of things-based air quality monitoring system that can identify pollutants such as CO2, NO2, and PM2.5 in real-time. The system that notifies users via a mobile application such as Telegram once the air quality exceeds a certain threshold is built with MQ-135 and DHT11 sensors. The study was conducted through an experiment with a development approach. Literature review, system design, prototyping, and performance evaluation are all part of this methodology. The results of the study show that the system can help monitor air quality and increase public awareness about the environment. Therefore, this study enhances efforts to reduce air quality pollution, especially in Indonesian cities.